Design of Interactive Web-Based Learning System For Chemistry Lesson (Case Study: Jakarta, SMA Muhammadiyah 4) - Muhammad Ichram; Irfan ,S. Kom, MMSI (Jurnal Sistem Informasi, 2010)
Progress of information and communication technology provides many facilities in human life.Today, the utilization of information technology policy and communications directed to solvethe problem of education in Indonesia. With the utilization of communication and informationtechnologies for education They allow for the construction of an interactive learning systemwhich helps in studying and understanding the theories, concepts, and procedures within aparticular field. One area worthy of study is developed to the level of chemical High School(SMA), the selection of study areas mentioned because of teacher difficulties in teaching anddelivering course material, thus affecting the lack of students' responses to the material. Webbasedinteractive learning system for chemistry lesson, the addition can assist and facilitate thestudents in the learning process can also assist educators in presenting the material withoutgoing through a face to face.